A study on mechanical and tribological properties of silicone rubber reinforced with white carbon black. (2nd January 2018) - He, Qiang; Li, Anling; Zhang, Yong; Liu, Songfeng; Guo, Yachen; Kong, Linghao
Abstract: This paper analysed the effect of different white carbon black (fumed silica and precipitated silica) on the mechanics and friction property of silicone rubber. The tensile strength, tearing strength, elongation rate and shore hardness of silicone rubber reinforced with different kinds or dosages of white carbon black were investigated in detail. The wear morphology, worn surface analysis and chemical compositions of the rubber sample after the friction test were analysed by means of scanning electron microscopy, three-dimensional profile metre and energy dispersive spectrometer, respectively. Results showed that the mechanics properties of silicone rubber were obviously enhanced with the increase in white carbon black content. Moreover, after the friction test, the vulcanised rubber reinforced with fumed silica has less wear surface protrusions and grinding than that of precipitated silica. The wear rubber filled with fumed silica surface is quite smooth and shows few furrows and grooves, which well corresponds to good anti-wear ability of the reinforcing fillers. In the course of practical application, it is necessary to take into account of the mechanical properties, wear resistance of rubber and the adding amount of filler to achieve the optimum coordination for the best mechanical and friction properties of silicone rubber.